Uzasadnienie aksjologiczne i historia obowiązywania zakazu reformationis in peius w polskiej procedurze karnej - Czerwińska, Dorota (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The paper aims at presenting the axiological and historical justification of the prohibition of reformatio in peius, which is currently provided for by article 434 of the Code of Criminal Procedure (c.c.p.). In the first part of the paper the author analyzes axiological justifications for this prohibition, mentioned by legal academics, dividing them into normative and psychological. The conclusion of that part is that the most convincing rationale is the one based on the right of the defense. The second part of the article presents the evolution of the normative model of reformatio in peius, including a brief analysis of relevant provisions of the codes of 1928, 1969 and 1997, also as modified by the recent amendments of the Act of the 27th September 2013. In the resume the author states that in the past the scope of the prohibition of reformatio in peius had been systematically broadened until 2003, when new exceptions were introduced for the purpose of streamlining the procedure.
Keywords: limits of appeal; the prohibition of reformatio in peius; legal axiology; legal history; appeal proceedings; right of defense of the accused